Book Reviews. Issue 3 (1st September 2013) - Benci, Jacopo; Peretti, Luca; Heim, Julia; Ferrari, Chiara; O'Rawe, Catherine; Orton, Marie; Welle, John P.; Laviosa, Flavia; Hennessey, Brendan
Michelangelo Red Antonioni Blue. Eight Reflections on Cinema, Murray Pomerance (2011) Berkeley: University of California Press, 300 pp., ISBN: 9780520258709, h/bk, 65, ISBN: 9780520266865, p/bk, 29.95Pavese e il cinema. Primo e ultimo amore, Franco Prono (2011) Acireale: Bonanno, 117 pp., ISBN: 978-8-87796-844-9, p/bk, €10Italian TV Drama & Beyond, Milly Buonanno (2012) Bristol, UK: Intellect, 264 pp., ISBN: 978-1-84150-459-9, p/bk, 30Terrorism, Italian Style. Representations of Political Violence in Contemporary Italian Cinema, Glynn Ruth, Giancarlo Lombardi and Alan O'Leary (2012) London : IGRS books, ISBN: 978-0-85457-228-1, p/bk, £25Italian Neorealist Cinema, Torunn Haaland (2012) Edinburgh: Edinburgh University Press, xii–235 pp., ISBN: 0748636110, h/bk, 105/£65Equivocal Subjects: Between Italy and Africa: Constructions of Racial and National Identity in the Italian Cinema, Shelleen Greene (2012) London: Continuum International Publishing Group, 328 pp., ISBN: 978-1-4411-9043-7, h/bk, 120The Great Black Spider on its Knock-Kneed Tripod: Reflections of Cinema in Early Twentieth-Century Italy, Michael Syrimis (2012) Toronto: Toronto University Press, Xiv–357 pp., ISBN: 978-1-4426-4401-4, h/bk, 85Ciak, si Puglia. Cinema di frontiera 1989–2012, Oscar Iarussi (2012) Bari: Laterza Edizioni della Libreria, v–xx, 3–92 pp., ISBN 978-8-84204-986-9, p/bk, €9Incontri cinematografici e culturali tra due mondi, Antonio Vitti (ed.) (2012) Pesaro: Metauro Edizioni, 670 pp., ISBN 978-88-6156-091-8, p/bk €25